The determinants of sustainable transportation in East Asian countries: Does the moderating role of institutional quality matter - Aden, Kadir; Dirir, Sadik Aden (Journal of Developing Economies, 2023)
Transportation has a profound effect on the environment, aggravating air pollution, climate change, and natural resource depletion. Additionally, the construction and maintenance of transportation infrastructure contribute to deforestation and habitat loss. Therefore, the aim of this research is to investigate the correlation between c02 emissions, natural resource depletion, trade, FDI inflow and transportation in a chosen number of eastern Asian countries, with a unique perspective of examining the influence of institutional qualities as a moderator among these factors. The analysis involves the utilization of CS-ARDL and dumitrescu-hurlin causality test to examine the data. The findings suggest that institutional qualities have a positive impact on the relationship between c02 emissions and transportation, reversing the negative association. Additionally, trade has a negative correlation with transportation, this can be explained by the fact that weak institutional quality can lead to corruption and a lack of transparency, which can discourage foreign investment and trade in the transportation sector. On the other hand, resource depletion and FDI inflows affect negatively the transportation services in East Asian countries. Therefore, the study highlights the significance of effective governance, regulation, and management of institutions in promoting better transportation planning and coordination, ultimately leading to sustainable transportation service.